ANALYSIS OF NOISE MEASUREMENTS IN THE WORK AREA TO THE OPERATOR'S HEARING IN THE PROCESS DEPARTMENT USING THE WORK SEMPLING METHOD - Bakhtiar Bakhtiar; Edi Yusuf; Muhammad Reza Fahlevi (Universitas Mulia, 2023)
PT. Ika Bina Agro Wisesa (IBAS) is one of the palm oil mills on the island of Sumatra, Indonesia. This palm oil factory is located in the village of Guha Uleue, Kuta makmur District, North Aceh District, Aceh province. The problem in this study is to identify and deal with the problems encountered by applying theory and concepts with work and idle calculations carried out using work sampling data on 3 operators in the Drying department. The research was carried out with the work and idle calculation time being carried out for 1 week. All Operators working on the production floor work from 08.00 to 16.00 with breaks from 12.00 to 13.00. The number of minutes from 08.00-12.00 and 13.00-16.00 means the total population in this study is 84. The purpose of this study is to analyze the measurement of noise in employees as seen from the effect of noise. The effect of noise will later be used to determine what is the influence of noise by each employee to complete his work in the process department. As for the results of this study there is an analysis of noise measurements using a Sound Level Meter (SLM) which has a noise level between 81.3 dB(A) to 88.9 dB(A). then PT. Ika Bina Agro Wisesa has a hearing protection program contained in the HSE Code of Practice-00612. The results of the study of measuring noise intensity 8 working hours for the operator position on Personal Noise Level dB (A) boiler 84.4, Personal Noise Level dB (A) polishing drum is 81.3, Personal Noise Level dB (A) ripple mill 88.9 and finally Personal Noise Level dB (a) The sterilizer is 67.7. this is in line with the Decree of the Minister of Manpower and Transmigration No. 13 of 2011 and the Decree of the Minister of Energy and Mineral Resources of the Republic of Indonesia No. 1827 of 2018 which is used to analyze and control noise in the processing plant area.